2020
DOI: 10.3390/ijerph17176231
|View full text |Cite
|
Sign up to set email alerts
|

Social Capital and Social Networks of Hidden Drug Abuse in Hong Kong

Abstract: Owing to the increasing prevalence of hidden drug abuse in Hong Kong, yet scarce relevant current local research, this study seeks to carry out an in-depth investigation into the experience of hidden drug abusers, paying particular attention to their relevance to social capital and social networks. Seventy-three abusers attending drug treatment programs were interviewed, and a thematic analysis was performed. The results indicate hidden drug abuse is popular in Hong Kong. Apart from the decline of public, larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…The validity and reliability of the Soulmate Scale make it a useful tool to assess the underlying factors that affect substance users to persistently take drugs. Assessing their inner-sense and their perception of drugs will provide valuable insights for formulating corresponding intervention plans to achieve drug abstinence, such as choosing suitable therapy in individual counselling to deal with substance users’ emotional loneliness, and group intervention to address their social loneliness by helping them to rebuild constructive social networks to facilitate their social reintegration and detach from the drug users network [ 38 ]. It is hoped that the scale can be applied in social service settings to assess the substance users’ psychological dependence on drugs.…”
Section: Discussionmentioning
confidence: 99%
“…The validity and reliability of the Soulmate Scale make it a useful tool to assess the underlying factors that affect substance users to persistently take drugs. Assessing their inner-sense and their perception of drugs will provide valuable insights for formulating corresponding intervention plans to achieve drug abstinence, such as choosing suitable therapy in individual counselling to deal with substance users’ emotional loneliness, and group intervention to address their social loneliness by helping them to rebuild constructive social networks to facilitate their social reintegration and detach from the drug users network [ 38 ]. It is hoped that the scale can be applied in social service settings to assess the substance users’ psychological dependence on drugs.…”
Section: Discussionmentioning
confidence: 99%
“…The law states that any person who transports manufactures, possesses (drugs and equipment), and cultivates dangerous drugs, can be sentenced to 3 years or up to imprisonment for life. Prior Triads' studies have already shown that the illegal drug market was already a mainstay for Triads due to the large profit margin; hence, their footprint was widely spread across both domestic and international illegal drug trading (Traver, 2009;Tracy, 1993;Chan et al, 2020). Under the blessing of the government's antidangerous drug efforts, the crime figure of serious drug offenses (mainly trafficking and manufacturing) dropped from 2,045 cases in 2011 to 740 cases in 2019; and 5,639 arrests to 2,399 arrests during the same period.…”
Section: Serious Drugs-related Crimesmentioning
confidence: 99%
“…Due to the increasing market demand and market expansion, dangerous drug trading became one of Triad's business expansion focuses during the pandemic. Prior Triads' studies have already shown that the illegal drug market was already a mainstay for Triads due to the significantly large profit margin; hence their footprint was widely spread across both domestic and international illegal drug trading (Traver, 2009;Tracy, 1993;Chan et al 2020).…”
Section: Serious Drugs-related Crimesmentioning
confidence: 99%
“…Previous studies have observed the role of network structure in predicting certain health outcomes such as transmission patterns of infectious diseases and sexual behaviours in networks [ 51 ] or contagion of health harming behaviors and outcomes within a network such as obesity [ 52 ], alcoholism and drug abuse [ 53 ]. Another important finding from our study is that in terms of network structure, the mean degree centrality scores ranged from 5.3 to 8.05 and were highest among networks with spousal support.…”
Section: Social Network Structure Characteristicsmentioning
confidence: 99%